PENGARUH KOMPOSISI AP TERHADAP PROSESIBILITAS SLURRY PROPELAN DENGAN KANDUNGAN ALUMINIUM TINGGI (EFFECTS OF AMMONIUM PERCHLORATE COMPOSITION ON HIGH CONTENT ALUMINIUM PROPELLANT SLURRY) - Afni Restasari; Rika Suwana Budi; Kendra Hartaya (Jurnal Teknologi Dirgantara, 2017)
As propellant solid contents, Ammonium perchlorate (AP) affect the fluid characteristics of propellant slurry that are important in mixing and casting process to produce homogenous solid propellant. Therefore, this research aims to find out the effects of Ammonium perchlorate compositions (fine AP (APh) : coarse AP(APk)) on the slurry`s fluid characteristics which are viscosity, pot life, and pseudoplasticity index. In this research, propellant A (APh : APk 1:2), propellant B (APh : APk 1:1), propellant C (APh : APk 3:2), and propellant D (APh : APk 2:1) were made. The methods include the measurement of viscosity by using Brookfield RVT viscometer spindle 07 at 0,3 rpm every 15 minutes. While, at 35th minute, the viscosity at 0,3; 0,5 and 0,6 rpm were measured. Based on the data of viscosity, graphs of ln viscosity vs time as well as viscosity vs shear rate were made to determine the equations of viscosity build-up and Power Law. It is known that the initial viscosity of propellants are 11,493 – 52945 P. The lowest viscosity and pot life (13,12 minutes) are shown by propellant A. While, pseudoplasticity index of propellants are 0,655 – 0,991. The lowest point is shown by propellant D and the highest point is shown by propellant B. Based on this index, propellant A is not suitable to be casted in vacuum. On the other hand, propellant C is relatively suitable to be improved because its viscosity  (17,506 P) and rate of increasing viscosity (247 P/minute) are not much different from propellant A. In addition, its pseudoplasticity index (0,972) is suitable for vacuum casting. The conclusion is that the correlation between APh : APk and fluid characteristics of of propellant slurry (viscosity, pot life and pseudoplasticity are various because of packing factor of particles in propellant composition. AbstrakSebagai padatan pengisi propelan, Ammonium perklorat (AP) dapat mempengaruhi sifat fluida dari slurry propelan yang penting dalam pencetakan untuk menghasilkan propelan yang homogen. Oleh karena itu, penelitian ini bertujuan untuk menemukan pengaruh komposisi AP (AP halus (APh): AP kasar(APk)) terhadap sifat fluida slurry yang meliputi viskositas, pot life dan indeks pseudoplastisitas. Dalam penelitian ini, dibuat slurry propelan A (APh : APk 1:2), propelan B (APh : APk 1:1), propelan C (APh : APk 3:2) dan propelan D (APh : APk 2:1). Metode yang digunakan meliputi pengukuran viskositas dengan viskometer Brookfield RVT spindle 07 pada 0,3 rpm setiap 15 menit. Sementara, di menit ke-35, viskositas pada 0,3; 0,5 dan 0,6 rpm diukur. Berdasarkan data tersebut, grafik ln viskositas vs waktu serta viskositas vs shear rate dibuat untuk menentukan persamaan viscosity build-up dan Power Law. Diketahui, nilai viskositas awal propelan dalam jangkauan 11.493 – 52945 P, dengan viskositas terendah dan pot life (13,12 menit) dimiliki oleh propelan A. Sementara, nilai indeks pseudoplastisitas propelan yang jangkauan 0,655 – 0,991, nilai terendahnya ditunjukkan oleh propelan D dan tertingginya ditunjukkan oleh propelan B, yang mana propelan A diketahui tidak sesuai untuk pencetakan dengan teknik vakum. Pada sisi lain, propelan C relatif baik untuk dikembangkan karena memiliki viskositas (17.506 P) dan laju kenaikan viskositasnya (247 P/menit) yang tidak berbeda jauh dengan propelan A, serta indeks pseudoplastisitas (0,972) sesuai untuk pencetakan dengan vakum. Disimpulkan, hubungan antara rasio APh : APk dengan sifat fluida propelan (viskositas, pot life dan pseudoplastisitas beragam oleh karena faktor packing dari partikel – partikel penyusun propelan.